Staged Fracturing of Horizontal Wells in Continental Tight Sandstone Oil Reservoirs: A Case Study of Yanchang Formation in Western Ordos Basin, China - Zhang, Dingxue; Liu, Yunfei; Luo, Hui; Cao, Shixue; Cao, Jingxin; Li, Xiao (Frontiers in Earth Science, 2021)
Continental tight sandstone oil reservoirs have strong heterogeneity, and staged fracturing technology of horizontal well is a crucial measure for successful development of oil and gas. In this study, the fracturing effect of horizontal wells in tight oil reservoirs of Yanchang Formation in the western Ordos Basin was systematically studied using the rock mechanics, array acoustic and microseismic testing data and the staged fracturing technology. The hydraulic fracturing method was used to calculate the horizontal principal stress difference (σH-σh). It showed that as the buried depth increases, σH-σh tends to decrease first and then increase. Small-scale fracturing should be used for areas with smaller σH-σh values. Fracturing construction parameters have an impact on oil production capacity, which is mainly manifested in that the usage of prepad fluid, sand-carrying fluid and proppant is proportional to productivity. Excessive displacement and construction scale should not be used in the fracturing process, and the fracture height of the target layer should be strictly controlled within the range of 26 m. The analysis of the "rupture points" in the fracturing curves shows that wells with relatively obvious rupture points usually have a higher oil production capacity. These wells have a good fracturing effect and an effective fracture network was formed in the tight oil reservoir. The optimization simulation results of the horizontal well pattern form show that the seven-point combined well pattern is the best well pattern, which is suitable for the development of tight oil sandstone in the Yanchang Formation.